Performance and reliability of exhaust gas recovery units for marine engines - Faіtar, Catalіn; Stan, Liviu-Constantin; Buzbuchi, Nicolae (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Although the marine diesel engine market is dominated by slow-coupled two-stroke engines with a direct coupling system and a crossover system or four-stroke engines with medium or high speeds, equipped with a reversing system, there is a hybrid variant that has always been used by the market in Japan and East Asia, especially by coastal or fishing operators. These are four-stroke slow engines. These types of engines are a specialty specific to the Japanese profile industry, being characterized by a simple and robust construction and fairly long piston strokes. The rated speeds of these motors do not exceed 200 rpm, which allows direct coupling to the propeller, eliminating the need for a reduction system. Compared to equivalent engines on the US or EU market, where medium or high speed four-stroke engines are preferred, the Japanese model has 6-cylinder in-line configurations, and the piston diameters of these engines may vary depending on the need for on market. For example, Akasaka Diesel built engines of the same type using piston diameters ranging from 220 mm to 510 mm, all with in-line 6-cylinder configuration.